The multilingual mind : a modular processing perspective - Sharwood Smith, Michael, 1942- (New York : Cambridge University Press, 2014)
'This book is the first detailed description of a particular theoretical framework for studying language development and language performance. The framework is called MOGUL (Modular On-line Growth and Use of Language). It has been the topic of numerous publications and presentations since the appearance of our 2004 keynote article in Bilingualism: Language & Cognition. MOGUL is not just about how a language grows in the individual child: it is about how the mind expands to accommodate more than one language both in childhood and later in life and how these various linguistic systems share space and interact'--
Introduction -- The language module : architecture and representations -- Processing in the language module -- Growth of the language module : acquisition by processing -- Beyond the language module -- The bilingual mind introduced -- The growth of a second language -- Consciousness and attention -- The role of consciousness in language growth -- Issues in SLA revisited -- Conclusion.
Includes bibliographical references and index.
Keywords: Multilingualism; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Kognition; Mehrsprachigkeit; Multilingualism